A 210-year tree-ring δ18O record in North China and its relationship with large-scale circulations. Issue 1 (1st January 2020) - Wang, Lu; Liu, Yu; Li, Qiang; Song, Huiming; Cai, Qiufang; Sun, Changfeng; Fang, Congxi; Liu, Ruoshi
Abstract: Tree-ring stable oxygen isotope (δ 18 OTR ) demonstrates the enormous potential for revealing hydrological climate changes and large-scale atmospheric circulations. Here, we established the 210-year δ 18 OTR chronology of Pinus tabulaeformis Carr. in Baotou, southwest Inner Mongolia, North China. The regional precipitation δ 18 O (δ 18 OP ) and June-July-August relative humidity (RHJJA ) were the two dominant environmental factors controlling the δ 18 OTR changes. Since the 1930s, the increasing δ 18 OTR values ​in the study region reflected the drying trend due to reducing precipitation and increasing temperature. The δ 18 OTR series in Baotou generally exhibited stronger correlations with three Indian summer monsoon (ISM) indexes than three East Asian summer monsoon (EASM) indexes during 1948–2009 AD. However, the δ 18 OTR record also significantly correlated with one EASM index. These results indicated that the Asian summer monsoon played an essential role in modifying the δ 18 OTR values, and the ISM possibly had more considerable influence compared with the EASM. We also found that the δ 18 OTR record had a higher correlation with the central-Pacific El Niño-Southern Oscillation (ENSO) than that with eastern-Pacific ENSO, probably because of the more substantial impact of the central-Pacific ENSO on the ISM.